Traces of social culture in the lived experiences of emotional eating among Iranian obese women - Ehteram Ebrahimi; Marjan Mardani-Hamooleh; Mehdi Khezeli; Manouchehr Avatef-Fazeli; Mojtaba Habibi-Asgarabad (BMC, 2024)
Abstract Introduction Emotional eating is a situation with harmful consequences for the physical, mental and social health of humans. In this regard, the present study aimed to explain the role of social culture in the lived experiences of emotional eating in Iranian obese women. Methods This was a qualitative study conducted using the phenomenological approach. Purposive heterogeneous sampling method was used to select 17 women with body mass index of 30 and above who had emotional eating experience. Data were collected through semi-structured and face-to-face interviews. A guideline designed by the research team, whose content validity was confirmed by the expert panel, was used to conduct the interviews. Data were analyzed based on Diekelmann 7-step approach, and trustworthiness was evaluated by Lincoln and Guba criteria. Results The main topic of the findings was social culture and emotional eating, which was explained by three themes: "influence of social culture", "language culture of eating" and "the culture of eating together". Influence of social culture had three sub-themes: "a legal and popular entertainment", "hospitality culture: encouraging guests to overeat", and "coping with the social stigma of thinness and obesity". The language culture of eating had two sub-themes of "association of common infinitives" and "the symbol of swallowing anger ". Also, "culture of eating together" included 2 sub-topics with the titles "pleasant symbol of belonging and love" and "the symbol of family cohesion". Conclusion This study found that social culture through language, norms, and customs can initiate and/or reinforce emotional eating. The results of this study can be used in the design of interventions to improve emotional eating behavior in women by emphasizing the characteristics of Iranian social culture.